Multi-hazard vulnerability for single-walled full-assembled underground stations. (February 2023) - Qiu, Tong; Chen, Xiangsheng; Su, Dong; Zhang, Jiqing; Xu, Zhenyan
Abstract: Full-assembled underground station (FUS) uses precast single-walled structure replacing traditional double-walled structure with overlapping diaphragm and exterior walls. The vulnerability of single-walled FUS against the urban multi-hazard factors is a critical unresolved problem. To fill this knowledge gap, this study proposed a single-walled FUS (FUS-1 W) multi-hazard vulnerability function for its first application in Shenzhen Metro. First, a full-scale test was performed on the precast single-walled structure. Second, multi-hazard finite element analysis (FEA) was performed for FUS-1 W and double-walled prefabricated underground station (PUS-2 W). Third, the vulnerability functions were constructed. The main conclusions include the following: (1) The test showed that the single-walled structure has significant performance recovery capability. (2) FEA results indicated multi-hazard effect was about 20 % higher than single-hazard. The deformation inclusiveness of FUS-1 W were twice of PUS-2 W in top and foundation zones, whereas it decreased to 50 % in structure zone. (3) The minor-damage probability of FUS-1 W were 23–36 % lower than that of PUS-2 W in top and foundation zones, whereas it was 28 % higher in structure zone. It is suggested that FUS-1 W be monitored to avoid aggravating damage and construction hazard should be closely monitored to alleviate the multi-hazard superposition effects. The research provide quantitative evaluation for the security management of single-walled FUS and have important application value for the promotion of FUS.